Comparative analysis of cow and buffalo milk based probiotic yoghurt formulations, for physicochemical, sensory, and in vitro biological activities - Muhammad Azhar Iqbal; Mian Anjum Murtaza; Aysha Sameen; Iram Hafiz; Ashiq Hussain; Tariq Aziz; Ashwag Shami; Nada K. Alharbi; Fahad Al-Asmari; Fakhria A. Al-Joufi (Food and Humanity, 2026)

Prevalence and cow-level risk factors for mild and severe subclinical mastitis in intensive and extensive dairy systems in Bangladesh - Muhammad Aktaruzzaman; M. Ariful Islam; Solama Akter Shanta; Mst. Tahomina Akter; Muhammad Tofazzal Hossain; Md. Nazmul Islam; Md. Shaffiul Alam; A. K. M. Anisur Rahman (Veterinary Research Communications, 2026)

Effect of increasing temperatures on duckweed growth, photosynthetic performance and frond ontogenesis - Muhammad Irfan; Muhammad Adil Chaudhry; Manuela Bog; Sándor Szabó; Ilona Mészáros; Marcel A. K. Jansen; Viktor Oláh (Plant Cell Reports, 2026)
Key message Duckweeds offer a suitable platform to study the effects of elevated temperatures on aquatic plants, and chlorophyll fluorescence imaging can reveal frond-level distribution of temperature stress. Abstract Temperature rise associated with climate change poses a major challenge for aquatic plants. It has a strong influence on their physiological performance and, consequently, their competitive ability and fitness. Yet comparative studies of impacts on different species remain scarce. This study investigated the effects of four different temperature regimes between 20 and 35 °C on five duckweed species ( Spirodela polyrhiza , Landoltia punctata , Lemna gibba , Lemna minor and Lemna minuta ) by integrating growth- and photosynthesis-based parameters. We also recorded spatial patterns of photosystem II efficiency within fronds using chlorophyll a fluorescence imaging to understand how temperature stress is distributed throughout the frond development. The results highlighted substantial inter-specific variation in thermal responses and underscore the importance of integrating physiological and growth-based indicators to predict aquatic plants’ responses to climatic warming. Through simultaneous measurement of growth performance, photosynthetic efficiency and within-frond heterogeneity, this study provides mechanistic insights into how rising temperatures may influence duckweeds. Such knowledge is essential for predicting future shifts in freshwater primary productivity, species dominance, biological invasions and ecosystem stability under the current global warming scenario.

Retraction Note: Ameliorating Nickel-Induced Stress in Hypophthalmichthys molitrix (Silver Carp) Through Piper nigrum Extract Supplementation - Syed Muhammad Farhan Ali Shah; Syed Makhdoom Hussain; Shafaqat Ali; Pallab K Sarker; Khalid A. Al-Ghanim; Sunakbaeva Dilara (Biological Trace Element Research, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Hyaluronic acid-functionalized liposomes as a nanoplatform for enhanced pharmacokinetics and therapeutic efficacy in arthritis - Zakir Ali; Muhammad Junaid; Sibgha Batool; Sidra Aslam; Tofeeq ur Rehman; Ali H. Alamri; Adel Al Fatease; Nabil K. Alruwaili; Majed A Alghamdi; Han-Gon Choi; Fakhar ud Din (Journal of Pharmaceutical Investigation, 2026)

Modulating the thermo-immuno-endocrine axis to alleviate heat stress in poultry: A pharmacological perspective - Mohamed E. Abd El-Hack; Ahmed I. Elsherbeni; Amira K. Hajri; Marzough A. Albalawi; Mohamed AbdElrahman; Mahmoud Moustafa; Mohammed Al-Shehri; Muhammad Asif Arain; Ismail E. Ismail (Journal of Thermal Biology, 2026)

A mixed carbonate-siliciclastic foreland basin system: An example from the Upper Cretaceous Muti Formation, Jabal-Akhdar Dome, Oman Mountains - Jenan Ahmed Attar; Iftikhar Ahmed Abbasi; Muhammad Hanif; Mohamed A. K. El-Ghali; Abdulrazaq Al-Sayigh; Mohamed S. H. Moustafa; Muhammad Qasim (Facies, 2026)

New frontiers in beverage fortification: Delivery of functional ingredients via micro- and nanoencapsulation in dairy and non-dairy beverages - Mohammad Rezaul Islam Shishir; Suliman Khan; Naymul Karim; Muhammad Bilal; Sarfaraz Hussain; Md Saifullah; Ahmed K. Rashwan; Haroon Elrasheid Tahir; Isam A. Mohamed Ahmed; Xinhua Zhang; Fujun Li (Food Research International, 2026)

Green-engineered CSPVA@CuO–Ag hybrid nanocomposite for methylene blue removal: a comprehensive adsorption study - S. K. Lakkaboyana; A. Muhammad; E. A. Abdelrahman; K. Neeli; P. Venkateswarlu; R. M. N. Kalla; A. G. Alhamzani (International Journal of Environmental Science and Technology, 2026)

Advancements in heterostructure electrolytes for Low-Temperature SOFCs, and the role of insulating a-Al2O3 in BaCe0.7Zr0.1Y0.1Yb0.1O3-δ-Based composites - Yuzheng Lu; Wenyu Li; Muhammad Khalid; M. A. K. Yousaf Shah; Chunhua Lu (Fuel, 2026)

Large-animal farmers’ knowledge, attitudes, and practices regarding antibiotic usage in dairy and beef fattening farms in Bangladesh’s milk pocket areas - Fardina Sultana Sumi; Kazi Rafiq; A. K. M. Anisur Rahman; Muhammad Tofazzal Hossain; Purba Islam; Md. Rakib Hasan; Shah Md. Iqbal; Anan Binte Zaman (Tropical Animal Health and Production, 2026)

Technological trends in rainwater harvesting for micro-hydropower: a scientometric review - S. N. F. Abdullah; M. K. A. Kamarudin; N. A. Wahab; N. Yaakub; A. S. Mohd Saudi; M. N. A. Rahman; S. Sunardi; F. Muhammad-Sukki; I. N. Ismail (International Journal of Energy and Water Resources, 2026)

Experimental investigation of the mechanical and thermal behaviors of shear connectors in concrete sandwich panels - Madyan A. Al-Shugaa; Khalid Mohamed; Abubakr E. S. Musa; Amin Al-Fakih; Ridha A. A. Alhasan; Mohammed A. Al-Osta; Muhammad K. Rahman; Mohammed Rizwan Ali (Innovative Infrastructure Solutions, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Rosa moschata leaf extract modulates complete freund’s adjuvant-induced polyarthritis in Wistar rats via regulation of pro-inflammatory and inflammatory biomarkers - Amr S. Abouzied; Uzma Saleem; Maryam Farrukh; Umme Farwa; Areej M. Alsolami; Fatima A. Jaber; Tourki A. S. Baokbah; Ibrahim Aljaezi; Nouf Abdullah Alharbi; Muhammad Ajmal Shah; Ana Sanchez Silva; Norah K. Algarzae (Inflammopharmacology, 2025)

Metabolite characterization of probiotic Enterococcus Faecium for targeting Salmonella Entrica gut bacteria causing gastroenteritis - Kashef Choudhary; Muhammad Naveed; Tariq Aziz; Syeda Izma Makhdoom; Muhammad Waseem; Nada K. Alharbi; Fatma Alshehri; Ashwag Shami; Maher S. Alwethaynani; Fahad Al-Asmari; Areej A. Alhhazmi; Fakhria A. Al-Joufi (Antonie van Leeuwenhoek, 2025)

Mechanistic insights into microplastic-induced reproductive toxicity in aquatic organisms: A comprehensive review - A K M Munzurul Hasan; Md. Foysul Hossain; Minhaz Uddin; Muhammad Tariq Khan; Uddin Md Saif; Mohamed Hamed; Christopher J. Martyniuk; Douglas P. Chivers (Aquatic Toxicology, 2025)

The Role of Silver Nanoparticles and Bacillus subtilis in Modulating Morpho–Physio–Biochemical Responses in Wheat (Triticum aestivum L.) Under Arsenic Stress - Mohammad K. Okla; Sadia Javed; Muhammad Faran Tahir; Ibrahim A. Saleh; Muhammad Anas; Muhammad Hamzah Saleem; Temoor Ahmed; Abdulrahman Abdullah Alatar; Bandar M. AlMunqedhi; Shafaqat Ali (Journal of Soil Science and Plant Nutrition, 2025)
Soil contamination with toxic heavy metals [such as arsenic (As)] is becoming a serious global problem because of the rapid development of the social economy. Although plant growth-promoting rhizo-bacteria (PGPR) and nanoparticles (NPs) are the major protectants to alleviate metal toxicity, the study of these chemicals in combination to ameliorate the toxic effects of As is limited. Therefore, the present study was conducted to investigate the effects of different levels of Bacillus subtilis (5 and 10 mg L –1 ) and silver (Ag)–NPs (10 and 20 mg kg –1 ) on morpho-physiological and antioxidative defense attributes, which was spiked with different levels of As [0 mM (i.e., no As), 100, and 200 mg kg –1 ] in wheat ( Triticum aestivum L.) seedlings. Results from the present study showed that the increasing levels of As in the soil significantly ( P < 0.05) decreased plant growth and biomass, photosynthetic pigments, gas exchange attributes, sugars, and nutritional contents from the roots and shoots of the plants. In contrast, increasing levels of As in the soil significantly ( P < 0.05) increased oxidative stress indicators in term of malondialdehyde (MDA), hydrogen peroxide (H 2 O 2 ), and electrolyte leakage (EL), and also increased organic acid exudation patter in the roots of T. aestivum . The negative impact of As toxicity can overcome the application of B . subtilis and Ag − NPs, which ultimately increased plant growth and biomass by capturing the reactive oxygen species (ROS), and decreased oxidative stress in T. aestivum by decreasing the As contents in the roots and shoots of the plants. Research findings, therefore, suggest that the combined application of B . subtilis and Ag − NPs can ameliorate As toxicity in T. aestivum , resulting in improved plant growth and composition under metal stress, as depicted by balanced exudation of organic acids. Graphical Abstract

Quantitative assessment of asymptomatic spinal cord compression using MRI: a multi-center study - Ali F. Khan; Sanaa Hameed; Alaa Baha; Fauziyya Muhammad; Grace Haynes; Amber Dastgir; Suresh K. Gulla; Hakeem J. Shakir; Michael L. Rohan; Yasin Y. Dhaher; Zachary A. Smith (GeroScience, 2025)

Insights into the development of visible-light-induced CeO₂-TiO₂/g-C₃N₄ heterojunction catalysts for the mitigation of antibiotic pollutants - Amal Abdulrahman; Abdullah K. Alanazi; Hessa A. Alsalmah; Sidra Mubeen; Noureddine Elboughdiri; Atef E.L. Jery; Adeel Ahmed; Muhammad Aadil (Journal of Water Process Engineering, 2025)

Correction to: Physiological and biochemical responses of the achachairu tree (Garcinia humilis) to the combined effects of salinity and flooding - Federico W. Sanchez; Jonathan H. Crane; Haimanote K. Bayabil; Ali Sarkhosh; Muhammad A. Shahid; Bruce Schaffer (Plant and Soil, 2025)

Physiological and biochemical responses of the achachairu tree (Garcinia humilis) to the combined effects of salinity and flooding - Federico W. Sanchez; Jonathan H. Crane; Haimanote K. Bayabil; Ali Sarkhosh; Muhammad A. Shahid; Bruce Schaffer (Plant and Soil, 2025)

Nutritional value and therapeutic applications of Chenopodium album for human and livestock health: A comprehensive review - Mohamed E. Abd El-Hack; Ahmed A. Allam; Ahmed K. Aldhalmi; Mahmoud Kamal; Muhammad Arif; Abdullah S. Alawam; Hassan A. Rudayni; Ayman E. Taha; Elwy A. Ashour; Mohammad M.H. Khan (Food Bioscience, 2025)

Experimental studies on CO2 sequestration via enhanced rock weathering in seawater: Insights for climate change mitigation strategies in coastal and open ocean environments - Arshad Ali; Muhammad I. Kakar; Mohamed A. K. El-Ghali; Hafiz Ur Rehman; Iftikhar A. Abbasi; Mohamed Moustafa (Acta Geochimica, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

PCSK9 and its relationship with HMGB1, TLR4, and TNFα in non-statin and statin-treated coronary artery disease patients - Dina A. Desouky; Nahla A. Nosair; Mohamed K. Salama; Mohammed A. El-Magd; Muhammad A. Desouky; Dalia E. Sherif (Molecular and Cellular Biochemistry, 2025)

Quantifying market prevalence, abundance, and suitable habitats of bulbuls in Java, Indonesia - Muhammad Ali Imron; Muhammad Tafrichan; Vincent Nijman; K. Anne-Isola Nekaris; Marco Campera; Febrian Edi Nugroho; Swiss Winasis; Riri Retnaningtyas; George A. Gale; Wanlop Chutipong (Biological Conservation, 2025)

RETRACTED ARTICLE: Ameliorating Nickel-Induced Stress in Hypophthalmichthys molitrix (Silver Carp) Through Piper nigrum Extract Supplementation - Syed Muhammad Farhan Ali Shah; Syed Makhdoom Hussain; Shafaqat Ali; Pallab K. Sarker; Khalid A. Al-Ghanim; Sunakbaeva Dilara (Biological Trace Element Research, 2025)

Comprehensive analysis of leak impacts on liquid-gas multiphase flow using statistical, wavelet transform, and machine learning approaches - Hicham Ferroudji; Muhammad Saad Khan; Abinash Barooah; Wahib A. Al-Ammari; Ibrahim Hassan; Rashid Hassan; Ahmad K. Sleiti; Sina Rezaei Gomari; Matthew Hamilton; Mohammad Azizur Rahman (Process Safety and Environmental Protection, 2025)

Impact of dairy wastewater on paddy rice cultivation, leachate microbes, and soil health under alternate wetting and drying irrigation - Juli Akter; Md. Touhidul Islam; Nusrat Jahan; Mohammed Mizanur Rahman; M. G. Mostofa Amin; Muhammad Tofazzal Hossain; A. K. M. Adham (Paddy and Water Environment, 2025)

The role of selenium and biochar nanoparticles in alleviating cadmium stress in wheat (Triticum aestivum L.) examined via morphophysiological traits and organic acid exudation patterns - Mohammad K. Okla; Sahar Mumtaz; Sadia Javed; Muhammad Hamzah Saleem; Ibrahim A. Saleh; Naser Zomot; Yasmeen A. Alwasel; Mostafa A. Abdel-Maksoud; Muhammad Adnan; Shafaqat Ali (South African Journal of Botany, 2024)

Drought Priming Enhanced Grain Yield of Wheat Against Salinity Stress - Ashutus Singha; Jahidul Karim; Asif Adnan Prince; Nargis Akter; khalada Akter Runa; Muhammad Naqib; A. K. Mohibul Islam; Setu Roy; Jouadul Hasan (Water Conservation Science and Engineering, 2024)

Effectiveness of biochar and wood vinegar from guava trees in controlling Fusarium verticillioides and enhancing growth and anatomical traits of maize (Zea mays L.) - Mansour M. El-Fawy; Ayman S. Saeed; Mohamed K. Abou-Shlell; Mahmoud A. Soliman; Esmat F. Ali; Ahmed A. Issa; Kamal A. M. Abo-Elyousr; Muhammad Imran; Asmaa S. El-Nagar (Journal of Plant Diseases and Protection, 2024)

Biosynthesis of Silver, Copper, and Their Bi-metallic Combination of Nanocomposites by Staphylococcus aureus: Their Antimicrobial, Anticancer Activity, and Cytotoxicity Effect - Mohsen A. Sayed; Tahany M. A. Abd El-Rahman; H. K. Abdelsalam; Sayed M. S. Abo El-Souad; Rawan Muhammad Shady; Radwa Abdallnasser Amen; Mostafa Ahmed Zaki; Martina Mohsen; Sara Desouky; Samar Saeed; Seif Omar; Asmaa A. H. El-Bassuony (Indian Journal of Microbiology, 2024)
The present study outlines an easy, cheap, and environmentally friendly way to make Staphylococcus aureus -mediated bimetallic silver-copper nanocomposites (Ag/Cu) that can fight cancer and germs. The gram-positive S. aureus synthesized Ag, Cu, and their bi-metallic nanocomposites extracellularly. We aimed to prepare the bimetallic nanocomposite in two different ways, and we compared them in terms of characterization and biological applications. The first one is a bimetallic nanocomposite (Ag/Cu b ) that was made by mixing Ag and Cu metal ions in equal amounts (50:50). Then, the whole mixture was reduced. The second is the after-reduction bimetallic nanocomposite (Ag/Cu a ), in which each metal ion was reduced separately, and then the nanocomposites were mixed (50:50%) during biological applications. Nanocomposites were characterized using UV–visible spectrophotometry, Fourier-transform infrared spectroscopy, dynamic light scattering, and transmission electron microscopy. The results demonstrated that surface plasmon bands were at 320 nm for Ag NPs and 525 nm for Cu NPs, and a shift from these peaks was observed at 290 nm in the Ag/Cu b bimetallic nanocomposite. The synthesized nanocomposites were confirmed to be in the nanoscale with 20, 40, and 80 nm spherical crystals, respectively. Nanocomposites were assayed for their antimicrobial activity against the gram-negative Pseudomonas aeruginosa , the acid-fast Mycobacterium smegmatis , the gram-positive Bacillus cereus, and S. aureus, in addition to three fungal species, which were Aspergillus flavus , A. fumigatus, and Candida albicans . The minimum inhibitory concentration and minimum bactericidal concentration were determined. The Ag/Cua/Cuaetallic nanocomposite was the most potent antimicrobial compound. The anticancer activity of the tested compounds was assayed against the hepatocellular carcinoma cell line (HepG-2). Low cytotoxic activity was recorded in most assayed nanocomposites against the baby hamster kidney cell line (BHK).

Snow leopard phylogeography and population structure supports two global populations with single refugial origin - Imogene A. Cancellare; Byron Weckworth; Anthony Caragiulo; Kristine L. Pilgrim; Thomas M. McCarthy; Alisher Abdullaev; George Amato; Xiaoxing Bian; Elena Bykova; Isabela Dias-Freedman; Mariya Gritsina; Lauren M. Hennelly; et al. (Biodiversity and Conservation, 2024)
Snow leopards ( Panthera uncia ) inhabit the mountainous regions of High Asia, which experienced serial glacial contraction and expansion during climatic cycles of the Pleistocene. The corresponding impacts of glacial vicariance may have alternately promoted or constrained genetic differentiation to shape the distribution of genetic lineages and population structure. We studied snow leopard phylogeography across High Asia by examining range-wide historical and contemporary genetic structure with mitochondrial DNA and microsatellite markers. We genotyped 182 individuals from across snow leopard range and sequenced portions of the mitogenome in a spatially stratified subset of 80 individuals to infer historical biogeographic and contemporary patterns of genetic diversity. We observed a lack of phylogeographic structure, and analyses suggested a single refugial origin for all sampled populations. Molecular data provided tentative evidence of a hypothesized glacial refugia in the Tian Shan-Pamir-Hindu Kush-Karakoram mountain ranges, and detected mixed signatures of population expansion. Concordant assessments of microsatellite data indicated two global genetic populations, though we detected geographic differences between historical and contemporary population structure and connectivity inferred from mitochondrial and microsatellite data, respectively. Using the largest sample size and geographic coverage to date, we demonstrate novel information on the phylogeographic history of snow leopards, and corroborate existing interpretations of snow leopard connectivity and genetic structure. We recommend that conservation efforts incorporate genetic data to define and protect meaningful conservation units and their underlying genetic diversity, and to maintain the snow leopard’s adaptive potential and continued resilience to environmental changes.

Influence of probiotic strains on growth performance, carcass characteristics and seasonal changes of growing New Zealand white rabbits - Elwy A. Ashour; Islam M. Youssef; Ahmed I. Elsherbeni; Muhammad Arif; Guillermo Tellez-Isaias; Ahmed K. Aldhalmi; Ayman A. Swelum; Mohamed E. Abd El-Hack (Tropical Animal Health and Production, 2024)

Consumer pesticide concerns and the choice of fruit and vegetable markets in five low- and middle-income countries - Justice A. Tambo; Monica K. Kansiime; Jayanthi R. Alaganthiran; Muhammad Danish; Solomon A. Duah; Shah Faisal; Makaiko G. Khonje; Fredrick Mbugua; Ganeshamoorthy Rajendran (Global Food Security, 2024)

Seed Priming with Taurine Debilitates Copper Phytotoxic Effects by Maintaining Redox Balance, Ions Homeostasis and Photosynthetic Efficiency in Canola (Brassica napus L.) - Sadia Zafar; Rizwan Rasheed; Umer Farooq; Muhammad Arslan Ashraf; Shafaqat Ali; Mohammed Ali Alshehri; Khalid A. Al-Ghanim; Pallab K. Sarker (Journal of Soil Science and Plant Nutrition, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Dietary nano-Selenium supplementation improves growth performance, nutrient digestibility and hematology in Cirrhinus mrigala fingerlings - Nisar Ahmad; Syed Makhdoom Hussain; Shafaqat Ali; Pallab K. Sarker; Khalid A. Al-Ghanim; Muhammad Mahmood (Journal of Trace Elements in Medicine and Biology, 2024)

An innovative perovskite oxide enabling improved efficiency for low-temperature ceramic electrochemical cells - Yuzheng Lu; M. A. K. Yousaf Shah; Naveed Mushtaq; Muhammad Yousaf; Nabeela Akbar; Naila Arshad; Sultan Irshad (Fuel, 2024)

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

Integrated facies analysis of the Late Cretaceous Simsima Formation in northwestern Oman mountain, Jabel Al-Rawdah, Hatta area, Oman - Mithaa Salim Al-Jabri; Iftikhar Ahmed Abbasi; Muhammad Hanif; Mohamed A. K. El-Ghali; Abdulrazaq Al Sayigh (Arabian Journal of Geosciences, 2024)

Correction to: Alleviation of cadmium toxicity in pea (Pisum sativum L.) through Zn−Lys supplementation and its effects on growth and antioxidant defense - Muhammad Hamzah Saleem; Abida Parveen; Shagufta Perveen; Naheed Akhtar; Fozia Abasi; Maria Ehsan; Habib Ali; Mohammad K. Okla; Ibrahim A. Saleh; Naser Zomot; Yasmeen A. Alwasel; Mostafa A. Abdel-Maksoud; et al. (Environmental Science and Pollution Research, 2024)

Wound healing, antioxidant and antibacterial activities of polyphenols of Psidium guajava L. leaves - Kainat Bilal; Fatima Mehboob; Nosheen Akhtar; Irfan Ali Mirza; Muhammad K. Okla; M. Junaid Dar; Ibrahim A. Saleh; Naser Zomot; Humaira Fatima (South African Journal of Botany, 2024)

Theoretical and experimental explored tailored hybrid H+/O2– ions conduction: Bridged for high performance fuel cell and water electrolysis - Zuhra Tayyab; Sajid Rauf; Muhammad Bilal Hanif; Hafiz Imran Ahmad Qazi; Naveed Mushtaq; Martin Motola; Sining Yun; Chen Xia; Dmitry A. Medvedev; Muhammad Imran Asghar; Abdullah N. Alodhayb; Arshad Hussain; et al. (Chemical Engineering Journal, 2024)

Alleviation of cadmium toxicity in pea (Pisum sativum L.) through Zn−Lys supplementation and its effects on growth and antioxidant defense - Muhammad Hamzah Saleem; Abida Parveen; Shagufta Perveen; Naheed Akhtar; Fozia Abasi; Maria Ehsan; Habib Ali; Mohammad K. Okla; Ibrahim A. Saleh; Naser Zomot; Yasmeen A. Alwasel; Mostafa A. Abdel-Maksoud; et al. (Environmental Science and Pollution Research, 2024)

Protein extracted from Moringa oleifera Lam. Leaves: Bio-evaluation and characterization as suitable plant-based meat-protein alternative - Muhammad Sameem Javed; Smara Qaiser Alvi; Adnan Amjad; Hasan Sardar; Muhammad Junaid Anwar; Asma Javid; Sami Abou Fayssal; Pankaj Kumar; Tracy Abou Fayssal; Saikh M. Wabaidur; Mohammad K. Okla; Ibrahim A. Saleh; et al. (Regulatory Toxicology and Pharmacology, 2024)

Antiplasmodial and antimicrobial activities of e nt -abietane diterpenoids from the roots of Suregada zanzibariensis - Jackson Obegi Matundura; Jacob O. Midiwo; Abiy Yenesew; Leonidah K. Omosa; Mallika Kumarihamy; Jianping Zhao; Mei Wang; Siddharth Tripathi; Shabana Khan; Veronica M. Masila; Vaderament-A. Nchiozem-Ngnitedem; Ilias Muhammad (Natural Product Research, 2023)

Novel sol–gel synthesis of Mo-doped ZnO-NPs for photo-catalytic waste water treatment using the RhB dye as a model pollutant - Muhammad Sohaib; Tahir Iqbal; Sumera Afsheen; M. B. Tahir; Arslan Masood; Muhammad Rafique; K. N. Riaz; M. A. Sayed; A. F. Abd El-Rehim; Atif Mossad Ali (Environment, Development and Sustainability, 2023)

Adsorption reduction of a gemini surfactant on carbonate rocks using formic acid: Static and dynamic conditions - Shams Kalam; Sidqi A. Abu-Khamsin; Shirish Patil; Mohamed Mahmoud; Muhammad Shahzad Kamal; Mobeen Murtaza; Kishore K. Mohanty (Fuel, 2023)

Only a Noise? The Role of Non-governmental Organizations in the Policy Processes of a New Social Forestry Model in Indonesia - Sari Rahayu; Dwi Laraswati; Dwiko B. Permadi; Muhammad A. K. Sahide; Ahmad Maryudi (Small-scale Forestry, 2023)

Combined Effect of Rice-Straw Biochar and Humic Acid on Growth, Antioxidative Capacity, and Ion Uptake in Maize (Zea mays L.) Grown Under Saline Soil Conditions - Zaffar Malik; Natasha Malik; Iqra Noor; Muhammad Kamran; Aasma Parveen; Muhammad Ali; Freeha Sabir; Hosam O. Elansary; Tarek K. Zin El-Abedin; Eman A. Mahmoud; Shah Fahad (Journal of Plant Growth Regulation, 2023)

A sustainable utilization of aquaculture wastewater for the production of commercially important tilapia fish and plants (mint and chickpea) in improved integrated aqua-agriculture system - A. Muhammad Alameen; K. Nanthini Devi; S. Dinesh Kumar; S. Gunabal; N. Krishnaveni; A. Gowthami; S. Sinduja; J. Roopavathy; P. Santhanam; G. Roseline Jebapriya; M. Saranya; A. Aravinth; et al. (Bioresource Technology Reports, 2023)

Bacillus Species as Direct-Fed Microbial Antibiotic Alternatives for Monogastric Production - Shifa A. Bahaddad; Meshal H. K. Almalki; Othman A. Alghamdi; Sayed S. Sohrab; Muhammad Yasir; Esam I. Azhar; Hichem Chouayekh (Probiotics and Antimicrobial Proteins, 2023)

Synthesis, biological evaluation, and molecular modeling studies of a new series of imidazothiazole or imidazooxazole derivatives as inhibitors of ectonucleoside triphosphate diphosphohydrolases (NTPDases) - Mahmoud K. Shehata; Muhammad Uzair; Seyed–Omar Zaraei; Afnan I. Shahin; Syed J. A. Shah; Saif Ullah; Jamshed Iqbal; Mohammed I. El–Gamal (Medicinal Chemistry Research, 2023)

Facile synthesis and comparative study of the enhanced photocatalytic degradation of two selected dyes by TiO2-g-C3N4 composite - Asma A. Alothman; Asif Ayub; Safa K. Hachim; Borhan Mustafa Mohammed; Farhat Hussain; Muhammad Altaf; Zainab Jawad Kadhim; Holya A. Lafta; Yasir S. Alnassar; Marwah A. Shams; Nada A. Almuhous; Mohamed Ouladsmane; et al. (Environmental Science and Pollution Research, 2022)

Abundance and richness of invertebrates in shade-grown versus sun-exposed coffee home gardens in Indonesia - Marco Campera; Budiadi Budiadi; Tomáš Bušina; Baladzuri Hafizh Fathoni; Janine Dermody; Vincent Nijman; Muhammad Ali Imron; K. A. I. Nekaris (Agroforestry Systems, 2022)
Complex agroforestry systems are suggested as a possible solution to reduce the effects of deforestation in the tropics while enhancing the livelihoods of local human populations. Coffee ( Coffea spp.) is one of the most important commodity crops in the world that can easily be cultivated in complex agroforestry systems. Coffee agroforestry systems usually sustain higher biodiversity levels than sun-exposed fields while keeping similar levels of productivity considering the several benefits of growing coffee under a complex system. We aim to explore the richness and abundance of invertebrates in coffee home gardens in West Java, Indonesia by comparing 14 sun-exposed and 14 shade-grown gardens. We collected data in March/April 2019 via pitfall traps, pan traps, and beating tray in each field. We ran generalised linear models to assess whether the number of species and the number of individuals of insects differed between sun-exposed vs. shade-grown coffee gardens, and tested associations between main taxa. Overall, there was no difference in the richness (sun-exposed: 19.86 ± SE1.19; shade-grown: 19.71 ± SE1.19; Z-value = 0.12, p value = 0.904) and abundance (sun-exposed: 141.93 ± SE 3.18; shade-grown: 139.93 ± SE3.16; Z-value = 0.35, p value = 0.706) of invertebrates in coffee gardens, although taxa specific differences were present. Sun-exposed fields had a higher abundance of invertebrates considered as pests (Blattodea: Rhinotermitidae, Ectobiidae; Coleoptera: Scarabaeidae, Lycidae and Tenebrionidae; Diptera: Anisolabididae, Drosophilidae and Sarcophagidae). Camponotus spp. were the most dominant ants in shade-grown gardens while Dolichoderus spp. and Myrmicaria spp. were more abundant in sun-exposed gardens. Despite the fact that sun-exposed coffee fields registered higher abundance of invertebrate pests than shade-grown coffee fields, the richness of invertebrates did not substantially vary between sun-exposed and shade-grown coffee, suggesting that the matrix of gardens offers advanced ecosystem services. It is important to keep the complexity of agroforestry systems that provide key habitats for biodiversity.

In Vitro Testing of Sunscreens for Dermal Absorption: Method Comparison and Rank Order Correlation with In Vivo Absorption - Yang Yang; Ann-Marie Ako-Adounvo; Jiang Wang; Sergio G. Coelho; Steven A. Adah; Murali K. Matta; David Strauss; Theresa M. Michele; Jian Wang; Patrick J. Faustino; Thomas O’Connor; Muhammad Ashraf (AAPS PharmSciTech, 2022)

Nanoemulsion-based dissolving microneedle arrays for enhanced intradermal and transdermal delivery - Muhammad Iqbal Nasiri; Lalitkumar K. Vora; Juhaina Abu Ershaid; Ke Peng; Ismaiel A. Tekko; Ryan F. Donnelly (Drug Delivery and Translational Research, 2022)
The development of dissolving microneedles (DMN) is one of the advanced technologies in transdermal drug delivery systems, which precisely deliver the drugs through a rapid dissolution of polymers after insertion into the skin. In this study, we fabricated nanoemulsion-loaded dissolving microneedle (DMN) arrays for intradermal and transdermal drug delivery. For this task, model drug (amphotericin B, AmB)-loaded nanoemulsion (NE) were prepared by the probe-sonication method. AmB-loaded-NE was prepared using Capmul MCM C-8 EP/NF, Tween ® 80, poly(vinyl alcohol) (PVA-10 kDa), and poly (vinyl pyrrolidone) (PVP-360 kDa or K29/32) by using SpeedMixer™, followed by probe-sonication and evaluated for particle size and polydispersity index (PDI). Transmission electron microscopy (TEM) was also used to assess the particle size before and after DMN casting. AmB-NE embedded DMN arrays were found to be strong enough, revealed efficient skin insertion, and penetrated down to the fourth layer (depth ≈ 508 μm) of Parafilm M ® (validated skin model). Ex vivo skin deposition experiments in full-thickness neonatal porcine demonstrated that after 24 h, AmB-NE-DMN arrays were able to deposit 111.05 ± 48.4 µg/patch AmB into the skin. At the same time, transdermal porcine skin permeation studies showed significantly higher permeability of AmB (29.60 ± 8.23 μg/patch) from AmB-NE-DMN compared to MN-free AmB-NE patches (5.0 ± 6.15 μg/patch) over 24 h. Antifungal studies of optimized AmB-NE-DMN, AmB-loaded discs and drug-free DMN against Candida albicans , confirmed the synergistic activity of Campul-MCM C-8, used in the nanoemulsion formulation. This study establishes that nanoemulsion based dissolving microneedle may serve as an efficient system for intradermal as well as transdermal drug delivery. Graphical abstract

The sticky tasty: the nutritional content of the exudativorous diet of the Javan slow loris in a lowland forest - Tungga Dewi; Muhammad Ali Imron; Ganis Lukmandaru; Katherine Hedger; Marco Campera; K. A. I. Nekaris (Primates, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Integration of Seed Priming and Biochar Application Improves Drought Tolerance in Cowpea - Muhammad Farooq; Leila Romdhane; Abdul Rehman; Amal K. M. Al-Alawi; Walid M. Al-Busaidi; Saeed A. Asad; Dong-Jin Lee (Journal of Plant Growth Regulation, 2021)

Chromium Exposure Causes Structural Aberrations of Erythrocytes, Gills, Liver, Kidney, and Genetic Damage in Striped Catfish Pangasianodon hypophthalmus - Sajida Akter Suchana; Md Shaker Ahmed; S. M. Majharul Islam; Muhammad Lutfar Rahman; Md Fazle Rohani; Tanzina Ferdusi; A. K. Shakur Ahmmad; Mst Kaniz Fatema; Muhammad Badruzzaman; Md Shahjahan (Biological Trace Element Research, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Evaluation of transfer of lead in soil plant animal system: assessment of consequences of its toxicity - Fu Chen; Jing Ma; Zafar Iqbal Khan; Kafeel Ahmad; Tasneem Ahmad; Ifra Saleem Malik; Asma Ashfaq; Mudasra Munir; Sonaina Nazar; Zunaira Munir; Abid Ejaz; Muhammad Nadeem; et al. (Environmental Science and Pollution Research, 2021)

Spatio-temporal variability of chlorophyll- a in response to coastal upwelling and mesoscale eddies in the South Eastern Arabian Sea - Muhammad Shafeeque; A. N. Balchand; Phiros Shah; Grinson George; Smitha B. R.; Eldho Varghese; Ajith K. Joseph; Shubha Sathyendranath; Trevor Platt (International Journal of Remote Sensing, 2021)

Human and ecological risk assessment of heavy metals in different particle sizes of road dust in Muscat, Oman - Hilal K. Al-Shidi; Hameed Sulaiman; Hassan A. Al-Reasi; Farrukh Jamil; Muhammad Aslam (Environmental Science and Pollution Research, 2021)

A missense allele of PEX5 is responsible for the defective import of PTS2 cargo proteins into peroxisomes - Muhammad Ali; Shahid Y. Khan; Tony A. Rodrigues; Tânia Francisco; Xiaodong Jiao; Hang Qi; Firoz Kabir; Bushra Irum; Bushra Rauf; Asma A. Khan; Azra Mehmood; Muhammad Asif Naeem; et al. (Human Genetics, 2021)

Machine Learning Outcome Prediction in Dilated Cardiomyopathy Using Regional Left Ventricular Multiparametric Strain - Robert M. MacGregor; Aixia Guo; Muhammad F. Masood; Brian P. Cupps; Gregory A. Ewald; Michael K. Pasque; Randi Foraker (Annals of Biomedical Engineering, 2021)

Efficacy of electrolyzed water against bacteria on fresh fish for increasing the shelf-life during transportation and distribution - Alam A. K. M. Nowsad; Nakib Dad Khan; Muhammad Mehedi Hasan; Syed Md Ehsanur Rahman; Toshiyoshi Araki; Takao Yoshimatsu (Journal of Consumer Protection and Food Safety, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Long‐term active restoration of extremely degraded alpine grassland accelerated turnover and increased stability of soil carbon - Yanfu Bai; Lina Ma; Abraham A. Degen; Muhammad K. Rafiq; Yakov Kuzyakov; Jingxue Zhao; Rui Zhang; Tao Zhang; Wenyin Wang; Xiaogang Li; Ruijun Long; Zhanhuan Shang (Global Change Biology, 2020)
Soil nutrient contents and organic carbon (C) stability are key indicators for restoration of degraded grassland. However, the effects of long‐term active restoration of extremely degraded grassland on soil parameters have been equivocal. The aims of this study were to evaluate the impact of active restoration of degraded alpine grassland on: (a) soil organic matter (SOM) mineralization; and (b) the importance of biotic factors for temperature sensitivity ( Q 10 ) of SOM mineralization. Soils were sampled from intact, degraded and restored alpine grasslands at altitudes ranging between 3,900 and 4,200 m on the Tibetan Plateau. The samples were incubated at 5, 15 and 25°C, and Q 10 values of SOM mineralization were determined. Structural equation modeling was used to evaluate the importance of vegetation, soil physico‐chemical properties and microbial parameters for Q 10 regulation. The Q 10 of N mineralization was similar among intact, degraded and restored soils (0.84–1.24) and was higher in topsoil (1.09) than in subsoil (0.92). The best predictive factor of CO 2 ‐ Q 10 for intact grassland was microbial biomass, for degraded grassland was basal microbial respiration, and for restored grassland was soil bulk density. Restoration by planting vegetation decreased the Q 10 of SOM mineralization as soil bulk density, the most important negative predictor, increased in restored grassland. The Q 10 of SOM mineralization in topsoil was 14% higher than in subsoil because of higher microbial abundance and exo‐enzyme activities. The NH 4 + content was greatest in intact soil, while NO 3 − content was greatest in degraded soil. The SOM mineralization rate decreased with grassland degradation and increased after long‐term (>10 years) restoration. In conclusion, extremely degraded grassland needs proper long‐term management in active restoration projects, especially for improvement of soil nutrients in a harsh environment.

Effect of hemoglobin polymorphism on performance traits in indigenous chicken genotypes in Nigeria - M. Orunmuyi; H. Muhammad; A. A. Musa; A. K. Olutunmogun; B. I. Nwagu (Tropical Animal Health and Production, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Formulation of Chitosan Polymeric Vesicles of Ciprofloxacin for Ocular Delivery: Box-Behnken Optimization, In Vitro Characterization, HET-CAM Irritation, and Antimicrobial Assessment - Ameeduzzafar; Nabil K Alruwaili; Syed Sarim Imam; Nasser Hadal Alotaibi; Nabil A. Alhakamy; Khalid Saad Alharbi; Sultan Alshehri; Muhammad Afzal; Sattam Khulaif Alenezi; Syed Nasir Abbas Bukhari (AAPS PharmSciTech, 2020)

Impact of interleukin IL-6 rs-1474347 and IL-10 rs-1800896 genetic polymorphisms on the susceptibility of HCV-infected Egyptian patients to hepatocellular carcinoma - Reham M. Abd El-Baky; Helal F. Hetta; Gopala Koneru; Marwa Ammar; Engy A. Shafik; Dina A Mohareb; Muhammad Abbas El-Masry; Haidi K. Ramadan; Mohamed Zakaria Abu Rahma; Michael A. Fawzy; Moustafa Fathy (Immunologic Research, 2020)

Towards a Web GIS-based approach for mapping a dengue outbreak - Muhammad A. Butt; A. Khalid; A. Ali; S. A. Mahmood; J. Sami; J. Qureshi; K. Waheed; A. Khalid (Applied Geomatics, 2020)

Core Competencies for Undergraduates in Bioengineering and Biomedical Engineering: Findings, Consequences, and Recommendations - John A. White; Donald P. Gaver; Robert J. Butera; Bernard Choi; Mary J. Dunlop; K. Jane Grande-Allen; Anna Grosberg; Robert W. Hitchcock; Aileen Y. Huang-Saad; Miiri Kotche; Aaron M. Kyle; Amy L. Lerner; et al. (Annals of Biomedical Engineering, 2020)

Structural styles, hydrocarbon prospects, and potential of Miano and Kadanwari fields, Central Indus Basin, Pakistan - Saif-Ur-Rehman K. Jadoon; Ding Lin; Siddique Akhtar Ehsan; Ishtiaq A. K. Jadoon; Muhammad Idrees (Arabian Journal of Geosciences, 2020)

Emergence and genetic analysis of variant pathogenic 4/91 (serotype 793/B) infectious bronchitis virus in Egypt during 2019 - Mohammed A. Rohaim; Rania F. El Naggar; Mohamed M. Hamoud; Abdel-Hamid I. Bazid; Abdulrhman M. Gamal; Samah E. Laban; Mohammed A. Abdel-Sabour; Shimaa A. E. Nasr; Manal M. Zaki; Muhammad Z. Shabbir; Osama K. Zahran; Muhammad Munir (Virus Genes, 2019)

Total Bioavailable Organic Selenium in Fishmeal-Based Diet Influences Growth and Physiology of Juvenile Cobia Rachycentron canadum (Linnaeus, 1766) - Hung Duc Pham; Muhammad A. B. Siddik; Ravi Fotedar; Chau Minh Nguyen; Ashfaqun Nahar; Sanjay K. Gupta (Biological Trace Element Research, 2019)

Variants in KIAA0825 underlie autosomal recessive postaxial polydactyly - Irfan Ullah; Naseebullah Kakar; Isabelle Schrauwen; Shabir Hussain; Imen Chakchouk; Khurram Liaqat; Anushree Acharya; Naveed Wasif; Regie Lyn P. Santos-Cortez; Saadullah Khan; Abdul Aziz; Kwanghyuk Lee; et al. (Human Genetics, 2019)

Periodic vicissitudes of different concentrations of a developed prototype killed S. aureus mastitis vaccine on immune modulators, mediators and immunoglobulins in cows - Idris Umar Hambali; Faez Firdaus Jesse Bin Abdullah; K. R. Bhutto; M. L. Mohd Azmi; A. H. Wahid; Z. Zakaria; M. N. Odhah; M. Arsalan; N. A. Muhammad; M. N. Jefri (Tropical Animal Health and Production, 2019)

Synthesis of 4-formyl pyridinium propylthioacetate stabilized silver nanoparticles and their application in chemosensing of 6-aminopenicillanic acid (APA) - A. Anwar; M. R. Shah; S. P. Muhammad; K. Ali; N. A. Khan (International Journal of Environmental Science and Technology, 2019)

Troubled waters: Threats and extinction risk of the sharks, rays and chimaeras of the Arabian Sea and adjacent waters - Rima W. Jabado; Peter M. Kyne; Riley A. Pollom; David A. Ebert; Colin A. Simpfendorfer; Gina M. Ralph; Shaikha S. Al Dhaheri; K. V. Akhilesh; Khadeeja Ali; Mohamud Hassan Ali; Tariq M. S. Al Mamari; K. K. Bineesh; et al. (Fish and Fisheries, 2018)
The extinction risk of sharks, rays and chimaeras is higher than that for most other vertebrates due to low intrinsic population growth rates of many species and the fishing intensity they face. The Arabian Sea and adjacent waters border some of the most important chondrichthyan fishing and trading nations globally, yet there has been no previous attempt to assess the conservation status of species occurring here. Using IUCN Red List of Threatened Species Categories and Criteria and their guidelines for application at the regional level, we present the first assessment of extinction risk for 153 species of sharks, rays and chimaeras. Results indicate that this region, home to 15% of described chondrichthyans including 30 endemic species, has some of the most threatened chondrichthyan populations in the world. Seventy‐eight species (50.9%) were assessed as threatened (Critically Endangered, Endangered or Vulnerable), and 27 species (17.6%) as Near Threatened. Twenty‐nine species (19%) were Data Deficient with insufficient information to assess their status. Chondrichthyan populations have significantly declined due to largely uncontrolled and unregulated fisheries combined with habitat degradation. Further, there is limited political will and national and regional capacities to assess, manage, conserve or rebuild stocks. Outside the few deepsea locations that are lightly exploited, the prognosis for the recovery of most species is poor in the near‐absence of management. Concerted national and regional management measures are urgently needed to ensure extinctions are avoided, the sustainability of more productive species is secured, and to avoid the continued thinning of the regional food security portfolio.

Mapping of novel salt tolerance QTL in an Excalibur × Kukri doubled haploid wheat population - Muhammad A. Asif; Rhiannon K. Schilling; Joanne Tilbrook; Chris Brien; Kate Dowling; Huwaida Rabie; Laura Short; Christine Trittermann; Alexandre Garcia; Edward G. Barrett-Lennard; Bettina Berger; Diane E. Mather; et al. (Theoretical and Applied Genetics, 2018)
Key message Novel QTL for salinity tolerance traits have been detected using non-destructive and destructive phenotyping in bread wheat and were shown to be linked to improvements in yield in saline fields. Abstract Soil salinity is a major limitation to cereal production. Breeding new salt-tolerant cultivars has the potential to improve cereal crop yields. In this study, a doubled haploid bread wheat mapping population, derived from the bi-parental cross of Excalibur × Kukri, was grown in a glasshouse under control and salinity treatments and evaluated using high-throughput non-destructive imaging technology. Quantitative trait locus (QTL) analysis of this population detected multiple QTL under salt and control treatments. Of these, six QTL were detected in the salt treatment including one for maintenance of shoot growth under salinity ( QG (1 – 5) .asl - 7A ), one for leaf Na + exclusion ( QNa.asl - 7A ) and four for leaf K + accumulation ( QK.asl - 2B.1 , QK.asl - 2B.2 , QK.asl - 5A and QK:Na.asl - 6A ). The beneficial allele for QG (1 – 5) .asl - 7A (the maintenance of shoot growth under salinity) was present in six out of 44 mainly Australian bread and durum wheat cultivars. The effect of each QTL allele on grain yield was tested in a range of salinity concentrations at three field sites across 2 years. In six out of nine field trials with different levels of salinity stress, lines with alleles for Na + exclusion and/or K + maintenance at three QTL ( QNa.asl - 7A , QK.asl - 2B.2 and QK:Na.asl - 6A ) excluded more Na + or accumulated more K + compared to lines without these alleles. Importantly, the QK.asl - 2B.2 allele for higher K + accumulation was found to be associated with higher grain yield at all field sites. Several alleles at other QTL were associated with higher grain yields at selected field sites.

Understanding the interactions of diruthenium anticancer agents with amino acids - Alexey A. Nazarov; Maria-Grazia Mendoza-Ferri; Muhammad Hanif; Bernhard K. Keppler; Paul J. Dyson; Christian G. Hartinger (JBIC Journal of Biological Inorganic Chemistry, 2018)

Potentially toxic elements in soil of the Khyber Pakhtunkhwa province and Tribal areas, Pakistan: evaluation for human and ecological risk assessment - Umar Saddique; Said Muhammad; Mohsin Tariq; Hua Zhang; Mohammad Arif; Ishtiaq A. K. Jadoon; Nimat Ullah Khattak (Environmental Geochemistry and Health, 2018)

Correction to: Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2018)
The original article was corrected. Author Muhammad Kundi should instead read: Muhammad Sohail.

Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2017)
To accelerate genetic gains in breeding, physiological trait (PT) characterization of candidate parents can help make more strategic crosses, increasing the probability of accumulating favorable alleles compared to crossing relatively uncharacterized lines. In this study, crosses were designed to complement “source” with “sink” traits, where at least one parent was selected for favorable expression of biomass and/or radiation use efficiency—source—and the other for sink-related traits like harvest-index, kernel weight and grains per spike. Female parents were selected from among genetic resources—including landraces and products of wide-crossing (i.e. synthetic wheat)—that had been evaluated in Mexico at high yield potential or under heat stress, while elite lines were used as males. Progeny of crosses were advanced to the F 4 generation within Mexico, and F 4 -derived F 5 and F 6 generations were yield tested to populate four international nurseries, targeted to high yield environments (2nd and 3rd WYCYT) for yield potential, and heat stressed environments (2nd and 4th SATYN) for climate resilience, respectively. Each nursery was grown as multi-location yield trials. Genetic gains were achieved in both temperate and hot environments, with most new PT-derived lines expressing superior yield and biomass compared to local checks at almost all international sites. Furthermore, the tendency across all four nurseries indicated either the superiority of the best new PT lines compared with the CIMMYT elite checks, or the superiority of all new PT lines as a group compared with all checks, and in some cases, both. Results support—in a realistic breeding context—the hypothesis that yield and radiation use efficiency can be increased by improving source:sink balance, and validate the feasibility of incorporating exotic germplasm into mainstream breeding efforts to accelerate genetic gains for yield potential and climate resilience.

Sensitivity of AGCM ‐simulated regional JJAS precipitation to different convective parameterization schemes - Muhammad Azhar Ehsan; Mansour Almazroui; Ahmed Yousef; O'Brien Enda; Michael K. Tippett; Fred Kucharski; Abdulrahman A. Alkhalaf (International Journal of Climatology, 2017)
This study examines the effects of convective parameterization schemes ( CPSs ) on the simulated June–September ( JJAS ) precipitation climatology, variability and predictability over southwestern Arabian Peninsula and northeast Africa during 1981–2014 within an atmospheric global climate model framework. The three CPSs used are: the simplified Arakawa–Schubert ( SAS ) scheme; the SAS scheme with Tokioka modification ( STOK ) and the Emanuel ( EMAN ) scheme coupled with a probability distribution function‐based cloud parameterization scheme. SAS and STOK overestimate JJAS total precipitation over the selected domain compared to observations, while EMAN underestimates. EMAN provides the most realistic distribution of precipitation and spatial distribution of convective precipitation despite the tendency for underestimating the total precipitation. The principal patterns of precipitation variability (as measured by the leading empirical orthogonal functions) in EMAN and STOK are clearly related to the observed pattern, while the maximum variability in SAS occurs in a completely different location. The El Niño Southern Oscillation‐related JJAS precipitation teleconnection simulated by the SAS scheme is very weak as compared to observations and other two CPSs . The signal‐to‐noise ratio estimated by SAS and STOK is very low as compared to EMAN . Correlation analysis shows that EMAN performs better than the other two CPSs . Low (high) outgoing longwave radiation ( OLR ) values are indicative of enhanced (suppressed) convection and hence more (less) cloud coverage. The root mean square error estimated for OLR in EMAN is lower than that of the other two CPSs . The vertical structure of specific humidity and temperature shows less error in EMAN than that of the other two CPSs , which could be a reason for better predictability over the region of interest.

Erratum to: Recent developments in immobilizing titanium dioxide on supports for degradation of organic pollutants in wastewater-A review - M. H. Alhaji; K. Sanaullah; A. Khan; A. Hamza; A. Muhammad; S. I. Mustapha; A. R. H. Rigit; S. A. Bhawani (International Journal of Environmental Science and Technology, 2017)

Recent developments in immobilizing titanium dioxide on supports for degradation of organic pollutants in wastewater- A review - M. H. Alhaji; K. Sanaullah; A. Khan; A. Hamza; A. Muhammad; M. S. Ishola; A. R. H. Rigit; S. A. Bhawani (International Journal of Environmental Science and Technology, 2017)

Classification of ankle joint movements based on surface electromyography signals for rehabilitation robot applications - Maged S. AL-Quraishi; Asnor J. Ishak; Siti A. Ahmad; Mohd K. Hasan; Muhammad Al-Qurishi; Hossein Ghapanchizadeh; Atif Alamri (Medical & Biological Engineering & Computing, 2017)

Skill and predictability in multimodel ensemble forecasts for Northern Hemisphere regions with dominant winter precipitation - Muhammad Azhar Ehsan; Michael K. Tippett; Mansour Almazroui; Muhammad Ismail; Ahmed Yousef; Fred Kucharski; Mohamed Omar; Mahmoud Hussein; Abdulrahman A. Alkhalaf (Climate Dynamics, 2017)

Molecular characterization of previously elusive badnaviruses associated with symptomatic cacao in the New World - Nomatter Chingandu; Muhammad Zia-ur-rehman; Thyail N. Sreenivasan; Surendra Surujdeo-Maharaj; Pathmanathan Umaharan; Osman A. Gutierrez; Judith K. Brown (Archives of Virology, 2017)

CDK5RAP2 interaction with components of the Hippo signaling pathway may play a role in primary microcephaly - Salil K. Sukumaran; Maria Stumpf; Sarah Salamon; Ilyas Ahmad; Kurchi Bhattacharya; Sarah Fischer; Rolf Müller; Janine Altmüller; Birgit Budde; Holger Thiele; Muhammad Tariq; Naveed Altaf Malik; et al. (Molecular Genetics and Genomics, 2017)

Microelectrophoretic study of environmentally induced DNA damage in fish and its use for early toxicity screening of freshwater bodies - Bilal Hussain; Tayyaba Sultana; Salma Sultana; K. A. Al-Ghanim; Shahreef Masood; Muhammad Ali; Shahid Mahboob (Environmental Monitoring and Assessment, 2017)

Characterization of carbon monoxide, methane and nonmethane hydrocarbons in emerging cities of Saudi Arabia and Pakistan and in Singapore - Barbara Barletta; Isobel J. Simpson; Nicola J. Blake; Simone Meinardi; Louisa K. Emmons; Omar S. Aburizaiza; Azhar Siddique; Jahan Zeb; Liya E. Yu; Haider A. Khwaja; Muhammad A. Farrukh; Donald R. Blake (Journal of Atmospheric Chemistry, 2017)

Cirrhotic patients have good insight into their daily functional impairment despite prior hepatic encephalopathy: comparison with PROMIS norms - Jasmohan S. Bajaj; Melanie B. White; Ariel B. Unser; Dinesh Ganapathy; Andrew Fagan; Edith A. Gavis; Richard K. Sterling; Douglas M. Heuman; Scott Matherly; Puneet Puri; Arun J. Sanyal; Velimir Luketic; et al. (Metabolic Brain Disease, 2016)

Response of Datura innoxia Linn. to Gamma Rays and Its Impact on Plant Growth and Productivity - Ibrahim M. Aref; Pervaiz R. Khan; Abdulaziz A. Al Sahli; Azamal Husen; M. K. A. Ansari; Mahmooduzzafar; Muhammad Iqbal (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

A comparative study of metal contamination in soil using the borehole method - T. L. Teh; Nik Norulaini Nik Ab Rahman; Mohammad Shahadat; Y. S. Wong; Muhammad I. Syakir; A. K. Mohd Omar (Environmental Monitoring and Assessment, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Using PCA in evaluating event-controlling attributes of landsliding in the 2005 Kashmir earthquake region, NW Himalayas, Pakistan - Muhammad Basharat; Abid Ali; Ishtiaq A. K. Jadoon; Joachim Rohn (Natural Hazards, 2016)

Synthesis and structural elucidation of two new series of aurone derivatives as potent inhibitors against the proliferation of human cancer cells - Aboubaker A. Elhadi; Hasnah Osman; Muhammad Adnan Iqbal; Sharmila K. Rajeswari; Mohamed B. Khadeer Ahamed; Amin M.S. Abdul Majid; Mohd Mustaqim Rosli; Ibrahim Abdul Razak; Aman Shah Abdul Majid (Medicinal Chemistry Research, 2015)

Structural styles, hydrocarbon prospects, and potential in the Salt Range and Potwar Plateau, north Pakistan - Ishtiaq A. K. Jadoon; Matthias Hinderer; Beenish Wazir; Rizwan Yousaf; Sher Bahadar; Muhammad Hassan; Zeeshan-ul-Hassan Abbasi; Sidra Jadoon (Arabian Journal of Geosciences, 2015)

Integrated effects of organic, inorganic and biological amendments on methane emission, soil quality and rice productivity in irrigated paddy ecosystem of Bangladesh: field study of two consecutive rice growing seasons - Muhammad Aslam Ali; M. A. Sattar; M. Nazmul Islam; K. Inubushi (Plant and Soil, 2014)

Synthesis of water soluble copper(II) complexes: crystal structures, DNA binding, oxidative DNA cleavage, and in vitro anticancer studies - Tan Yi Han; Teoh Siang Guan; Muhammad Adnan Iqbal; Rosenani A. Haque; K. Sharmila Rajeswari; Mohamed B. Khadeer Ahamed; A. M. S. Abdul Majid (Medicinal Chemistry Research, 2014)

Changes in extreme temperature and precipitation in the Arab region: long‐term trends and variability related to ENSO and NAO - M. G. Donat; T. C. Peterson; M. Brunet; A. D. King; M. Almazroui; R. K. Kolli; Djamel Boucherf; Anwar Yousuf Al‐Mulla; Abdourahman Youssouf Nour; Ahmed Attia Aly; Tamer Ali Ali Nada; Muhammad M. Semawi; et al. (International Journal of Climatology, 2014)
A workshop was held in Casablanca, Morocco, in March 2012, to enhance knowledge of climate extremes and their changes in the Arab region. This workshop initiated intensive data compilation activities of daily observational weather station data from the Arab region. After conducting careful control processes to ensure the quality and homogeneity of the data, climate indices for extreme temperatures and precipitation were calculated. This study examines the temporal changes in climate extremes in the Arab region with regard to long‐term trends and natural variability related to ENSO and NAO . We find consistent warming trends since the middle of the 20th Century across the region. This is evident in the increased frequencies of warm days and warm nights, higher extreme temperature values, fewer cold days and cold nights and shorter cold spell durations. The warming trends seem to be particularly strong since the early 1970s. Changes in precipitation are generally less consistent and characterised by a higher spatial and temporal variability; the trends are generally less significant. However, in the western part of the Arab region, there is a tendency towards wetter conditions. In contrast, in the eastern part, there are more drying trends, although, these are of low significance. We also find some relationships between climate extremes in the Arab region and certain prominent modes of variability, in particular El Niño‐Southern Oscillation ( ENSO ) and North Atlantic Oscillation ( NAO ). The relationships of the climate extremes with NAO are stronger, in general, than those with ENSO , and are particularly strong in the western part of the Arab region (closer to the Atlantic Ocean). The relationships with ENSO are found to be more significant towards the eastern part of the area of study. © 2013 Royal Meteorological Society

Python Erythrocytes Are Resistant to α-Hemolysin from Escherichia coli - Casper K. Larsen; Marianne Skals; Tobias Wang; Muhammad U. Cheema; Jens Leipziger; Helle A. Praetorius (The Journal of Membrane Biology, 2011)

Determination of Arsenic in Scalp Hair of Children and its Correlation with Drinking Water in Exposed Areas of Sindh Pakistan - Tasneem G. Kazi; Jameel A. Baig; Abdul Q. Shah; Muhammad Balal Arain; Muhammad Khan Jamali; Ghulam A. Kandhro; Hassan I. Afridi; Nida F. Kolachi; Sumaira Khan; Sham K. Wadhwa; Faheem Shah (Biological Trace Element Research, 2011)

Spectral analysis of local climatic fluctuations - Muhammad J. Iqbal; J. Quamar; M. A. K. Yousufzai (Arabian Journal of Geosciences, 2011)

Targeted therapy for oesophageal cancer: an overview - K. N. Syrigos; A. Zalonis; E. Kotteas; Muhammad Wasif Saif (Cancer and Metastasis Reviews, 2008)

Time Course of Processes Underlying Picture and Word Evaluation: An Event-Related Potential Approach - Allen Azizian; Todd D. Watson; Muhammad A. Parvaz; Nancy K. Squires (Brain Topography, 2006)